2013
DOI: 10.1080/14616734.2013.804329
|View full text |Cite
|
Sign up to set email alerts
|

Measuring scripted attachment-related knowledge in middle childhood: the Secure Base Script Test

Abstract: Secure base scripts (SBS) are thought of as the earliest, rudimentary mental representations of attachment, comprising temporally and causally related events occurring in interactions between children and their attachment figures. SBS have been studied in preschool children, adolescents and adults, but there is little research relating SBS to other attachment measures in middle childhood. Here, the Secure Base Script Test (SBST), a narrative-based measure of attachment scripts in middle childhood, was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
108
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(122 citation statements)
references
References 34 publications
7
108
4
1
Order By: Relevance
“…Although both ECR-RC [29] and PIML [26] have excellent psychometric properties, attachment researchers traditionally advocate the use of interview measures like the Child Attachment Interview [40]. However, recent research [41] has shown that self-reported attachment and narrative attachment measures are significantly correlated in childhood. These findings suggest that self-reported measures might be a valid way to measure attachment in this specific age-group.…”
Section: Discussionmentioning
confidence: 99%
“…Although both ECR-RC [29] and PIML [26] have excellent psychometric properties, attachment researchers traditionally advocate the use of interview measures like the Child Attachment Interview [40]. However, recent research [41] has shown that self-reported attachment and narrative attachment measures are significantly correlated in childhood. These findings suggest that self-reported measures might be a valid way to measure attachment in this specific age-group.…”
Section: Discussionmentioning
confidence: 99%
“…Children’s secure base script scores were significantly associated with both mood (child report) and emotion regulation (teacher report). Further, Psouni and Apetroaia (2014) examined convergent validity between the secure base script construct using the Secure Base Script Test (SBST) and the Kerns Security Scale (KSS; e.g. Kerns, Klepac, & Cole, 1996) and the Friends and Family Interview (FFI; Kriss, Steele, & Steele, 2012) in a large middle childhood sample.…”
Section: Script-like Attachment Representationsmentioning
confidence: 99%
“…describing a mother and child spending a morning playing together) provided reliable assessments of secure base script use in a sample of adolescents. More recently, the ASA has been successfully revised for middle childhood samples (Psouni, & Apetroaia, 2014; Waters, Bosmans, Vandevivere, Dujardin, & Waters, 2015). Both Dykas et al (2006) and Steele et al (2014) found that adolescent ASA script scores were significantly correlated with established measures of adult attachment (e.g., Adult Attachment Interview, AAI, George et al, 1985; Experiences in Close Relationships–Revised questionnaire, ECR-R, Fraley et al, 2000) and had similar patterns of associations with parental sensitivity measures from infancy through early adolescence and early attachment histories as did scale scores derived from the AAI completed by these SECCYD participants.…”
mentioning
confidence: 99%